IMPROVING THE MECHANISM FOR FORMING AND DISTRIBUTING LOCAL BUDGET RESERVE FUNDS IN THE SUSTAINABLE FINANCING OF THE SOCIAL SPHERE - Turmankulov Norpulat Sadullaevich; Abdumalikov Abdukhakim Abduvalievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article provides a scientific analysis of the role and importance of local budget reserve funds in the sustainable financing of the social sphere. The mechanisms for forming and distributing reserve funds are examined, and the existing problems are identified. Based on the research findings, scientific and practical proposals for improving these mechanisms have been developed.